Statutory Assessment for Special Educational Needs and the Warnock Report; the First 40 Years - Lamb, Brian (Frontiers in Education, 2019)
The Warnock report ‘Special Educational Needs’ (Warnock 1978) provided the catalyst for an enduring framework of individual statutory assessment in England for children and young people (CYP) with Special Educational Needs (SEN). . Through its implementation in the Education Act 1981, consolidated in the Education Act 1966, the report established the overall SEN framework in England for last 40 years; laying the foundation for statements of SEN and more recently Education Health and Care Plans (EHCPs). The underlying legal structure created by Warnock has been reinforced rather than changed with the introduction of the Children and Families Act 2014. However by establishing rights to specified levels of resources, at the level of individual provision, the Warnock framework has risked undermining adequate provision and parental confidence in Special Educational Needs and Disability (SEND) provision overall-a central paradox of the SEND framework. This paper considers the consequences of an over reliance on statutory assessment to secure provision, the extent to which it skews resources within the system to one group of children and is therefore in danger of undermining the overall objectives of the current SEND reforms. However it is difficult to reform the statutory system without creating greater parental confidence in the non-statutory offer. While additional legislation to strengthen the SEND framework is desirable the Government could address the overreliance on statutory assessment by a more rigorous implementation of current legislation linked to reforms in funding, accountability and a renewed focus on the Equality Act 2010 provisions on SEND. This would entail the Government being willing to support a more rights based and less market led approach in schools and other settings and introduce strategies to reduce the reliance on statutory assessment in favor of ensuring the education system could routinely meet more CYPs needs. The conclusions are focused on the English system of SEND but the solutions are of relevance for other SEND assessment and funding models which are also considered.